As matemáticas mobilizadas pelos moradores do assentamento pa-baviera no processo de produção da farinha de mandioca. - SOUSA, Kalyta Gabriela Coelho. (Universidade Federal do Tocantins, 2024)
This study was developed through an investigation about the production of flour in the Ethnomathematics perspective, in order to question: which mathematics are mobilized by the flour producers of the Baviera Settlement Project? To answer this question, we aimed to understand which mathematics the settlers use during the flour production process. The research in question was developed in the Baviera Settlement Project, located in the municipality of Aragominas, state of Tocantins, based on a qualitative approach anchored in ethnography and using observation techniques and narrative interviews, so that together with the participants we could describe their practices in dealing with everything from land preparation to the marketing of cassava flour. To this end, we sought to carry out readings in the field of Ethnomathematics, in order to broaden our views and reflections on how mathematical knowledge occurs in the rural context of small producers, in this case, of cassava flour. Through this research, it was noticed that during the flour making process, producers mobilize an informal Mathematics that has a relationship with school Mathematics, particularly with area contents, unit of measurement magnitudes, basic fundamental operations and the rule of three simple ones, which they use during all stages of the process.